DAMPAK PARIWISATA DI KAWASAN PANTAI PADANG TERHADAP MANAJEMEN RISIKO BENCANA GEMPA DAN TSUNAMI - Suryadi, Meity Intan; Enzelluthfiyah, Liza; Amalia, Haya Shaliha; Pratiwi, Wiwik Dwi (JURNAL DARMA AGUNG, 2024)
Disaster risk mitigation in the tourism industry has a prominent role in maintaining the sustainability and security of tourism destinations and the tourism industry as a whole. One of the strategic areas of Padang City that has an important influence on environmental preservation and disaster mitigation is the strategic area along Padang Beach. This research aims to identify the impact of tourism in the Padang Beach area on earthquake and tsunami disaster risk management based on the stages of disaster management. This research uses a qualitative descriptive approach through literature study. Data were obtained from scientific journals, books, statistical reports, news, and policy documents. The results of this research show that tourism activities at Padang Beach area have a significant impact on the implementation of earthquake and tsunami disaster risk management in Padang City. The higher level of tourist visits to tourist attractions, the higher risks they will face. In the Padang Beach area, there are infrastructure, facilities, and infrastructure to support disaster evacuation as a mitigation effort. On the other hand, community and tourist preparedness have been strengthened in the Padang Beach area through stakeholder collaboration.